Publicação científica derivada das dissertações e teses na interface entre educação física e educação especial - Sacardo, Michele Silva (2006)
Knowing if the dissertations and thesis, after the defense, generated other kinds of publications that reached of a broader way the population-target of the studies carried out, it s intimately related to social relevance of the searches produced in the postgraduate studies. It s believed that this study can contribute to areas of Special Education and Physical Education, in the sense of making possible to scientific community having a knowledge more systematic about the social validity and, principally, the application of the knowledge produced in the field of the master s degree and doctorate of these areas in this country. This study main to analyze scientific publications derived from dissertation and thesis in Physical and Special Education that had resulted in articles, books and chapters of books with thematic towards people with special needs. For the development of the study was adopted a methodology divided into the following fazes: a)The constitution of the theoretical corpus of the research was carried by literature revision on: production of the scientific knowledge in the areas of Physical Education, Special Education and Science of the Information; science, scientists and scientific knowledge; scientific communication; scientific publication; valuation of the scientific production and reflections concerning the evaluation of the after-graduation; b) Identification of Postgraduate Programs studies in Physical Education and Special Education; b) data collection in the Capes site, at the NUTESES and PPGEEs; c) databases elaboration for systematization of the collected data; d) Description and analysis of the results carried through to the light of the theoretical reference. The results had shown that 58% of publications generated for the thesis and thesis had been published under the article form, followed by chapters (29%) and books (13%). These confirm what the previous literature references indicate, or either that, the publication channel more used by the researchers to promote their works is the scientific article publication in periodic.